Supervisor and interpersonal relations [filem jalur] - Resources for Education and Management (Resources for Education and Management for Addison-Wesley Pub, 1970)
Contents : 1. General problems. 2. Relationships between peers. 3. Attitudes toward subordinates. 4. Attitude toward supervision. 5. Reducing conflict.